Polyurethane-epoxy based azopolymers: Influence of chemical structure over photoinduced birefringence - Sáiz, Luciana María (2012)
A comparative study of the influence of the competitive reactions that can take place in epoxy-isocyanate based azo systems over optical behavior was developed. Diverse disperse red 19 (DR 19) azo urethane oligomers (PUs) were synthesized and characterized using size exclusion chromatography (SEC), Fourier transform infrared (FTIR), and UV-visible spectroscopy. Based on these urethane oligomers, epoxy-PU networks having isocyanurate and oxazolidone rings in their structures were prepared in different isocyanate/epoxy stoichiometric ratios, r = eq. NCO/eq. epoxy (0.5, 1, and 2). Photoinduced anisotropy, remnant birefringence and dichroism were measured for the resulting polymers and evaluated as function of their Tgs and chemical structures. Final materials exhibited very high values of maximum birefringence and RB being promised materials for using in optical storage information devices.